Сварочный преобразователь - Сипайлов Г. А. Геннадий Антонович; Лоос А. В. Александр Владимирович; Гумовский Ю. Н. Юрий Никитич; Яковлев А. А. Алексей Алексеевич; Федоренко Г. А. Глеб Афанасьевич
опубл. 30.12.80